Skillful and strategic navigation in soccer – a motor-cognitive dual-task approach for the evaluation of a dribbling task under different cognitive load conditions - Klotzbier, Thomas J.; Schott, Nadja (Frontiers in Psychology, 2024)
Soccer is a competitive sport that relies on distinct motor skills and cognitive processes. However, cognitive aspects are often overlooked, with a focus mainly on motor skills. Limited research has explored screening tests within motor-cognitive navigation dual-task (DT) paradigms. This study aims to validate a sensitive approach for assessing soccer-specific dribbling by evaluating the Trail-Dribbling Test (TDT) as a method to differentiate high-performance (HP) from low-performance (LP) players. Two hundred and seventy-five participants (41 females) aged between 12 and 34 completed the Trail-Making Test (TMT), the Trail-Walking Test (TWT), and the soccerspecific TDT under three levels of cognitive load. Results indicated shorter TDT durations for HP compared to LP players, with increased cognitive load accentuating differences (TDT-M: p = .044, d = .260; TDT-A: p < .001, d = .449; TDT-B: p < .001, d = .653). The TDT effectively discriminated between HP and LP players in the 14-15 (AUC = .712 -.820) and 16-17 age groups (AUC = .634 -.839). In conclusion, the ecologically valid TDT demonstrates the potential for quantifying soccerspecific dribbling, offering insights into motor and cognitive aspects of dribbling performance, especially among soccer players aged 14-17.Most test procedures for assessing fundamental skills in soccer overlook the relevant cognitive components in a soccer game. This research aims to tackle this issue by utilizing a DT paradigm to investigate soccer-specific dribbling while also considering the pertinent cognitive processes.